The conceit of ‘color hearing’ in literary studies of a song text - Naumenko, Nataliia (My University, 2017)
The article represents the results of stylistic and literary analysis of The Wild Wild Sea, a song lyric by Sting. There was shown that the contemporary critical studies of any literary work may involve the elements of other scientific paradigms to create the new vision of an artistic phenomenon. У статті наведено результати стилістичного та літературного аналізу пісенного твору Стінга "Бурхливе море". Показано, що сучасні літературознавчі дослідження будь-якого пісенного тексту можуть включати елементи інших наукових парадигм із метою створити нове бачення художнього феномену.
Keywords: department of humanities; song; hearing; lyrics; works by Sting; color; кафедра гуманітарних дисциплін; пісня; слух; лірика; творчість Стінга; колір; песня; лирика; творчество Стинга; цвет